Information about sun exposure, protection, awareness and behavioural patterns of medical students in Kolar - Shruthi Madhavi Govindarajulu; Rajashekar Taları Srinivas; Suresh Kumar Kuppuswamy; Priya Prem (Galenos Publishing House, 2020)
Background and Design: The harmful ultraviolet radiation of sunlight can damage skin cells and affect the skin's normal appearance. The short term effects associated with sun exposure include acute skin damage associated changes such as sunburn, suntan and the long term effects are delayed pigmentation, impaired vitamin D synthesis, altered immunological responses of the skin, photodamage and photocarcinogenesis. The majority of these photodermatoses are preventable with the implementation of appropriate sun protection measures and behavioral changes. Materials and Methods: Data collection was done with the help of a structured questionnaire which was distributed among 339 undergraduate medical students in their 4th, 7th, 8th and 9th term attending dermatology postings at a medical college attached to a tertiary hospital from January 2018 to July 2018. Results: The majority of the students in this study were 4th term undergraduates representing 35.3% of the population. The mean ± standard deviation scores of knowledge, behaviour and awareness were 11.67±3.31, 12.32±5.004, 24±6.282, respectively. Only 26.8% of the above population always used sunscreen during daily activities, 32.1% sometimes, 25.6% rarely used and 15.3% never used sunscreen during daily activities. One-Way ANOVA tests depicted a statistically significant difference among the various term students with respect to variables of knowledge, behaviour and awareness score with a p<0.001. Conclusion: The results of this study indicate that knowledge regarding sun exposure and its adverse effects, behaviour and awareness even among medical students to sun protection is inadequate. Sun protection should start at an early age and therefore awareness campaigns are highly recommended.